Assessing the Impact of Mobile Phone Usage on Mental Health, Biochemical Stress Markers and Academic Performance of Medical Students of Sheikh Zayed Medical College Rahim Yar Khan - Ghazala Yasmeen Iqbal, Nadia Saman, Sadia Nikhet, Farrukh Adeel, Naila Jabeen, Tariq Hussain (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Mobile phones have revolutionized the way we communicate, access information, and navigate our daily lives. Medical students, in particular, have embraced mobile technology as a vital tool for learning, socialization, and stress management. However, the excessive use of mobile phones has raised concerns about its impact on physical and mental health, as well as academic performance. Medical students are already vulnerable to high levels of stress, anxiety, and burnout due to the demands of their rigorous academic programs. Objectives: The objective of the study is to investigate the relationship and the impact between mobile phone usage and health outcomes (stress, anxiety, sleep quality) and academic performance (marks, study habits) among medical students of Sheikh Zayed Medical College Rahim Yar Khan. Methodology: A cross-sectional study was conducted on medical students of all five years of Sheikh Zayed Medical College, Rahim Yar khan. Sample of 270 MBBS students of Sheikh Zayed Medical College from 1st year MBBS to final year MBBS was taken in this study. Data was collected from 270 medical students interpersonally through hard copy. Data was analyzed using SPSS version 23 software and results were interpreted in the form of tables and figures. Results: During the period of inquiry, medical students of Sheikh Zayed Medical College were investigated for the purpose of impact on their academic performance as well as their health by the usage of mobile phones. Total 270 students of SZMC participated in research. Out of which 82.6% students are of age 20-25 years of age. 82 students are of 1st year MBBS, 42 of 2nd year MBBS, 46 of 3rd year MBBS, 54 of 4th year MBBS and 46 of final year MBBS. More than half of students uses mobile phone for more than 4hrs/day, 41.7% males and 39.4% females stated decline in their academic performance by using mobile phone. 43.7% students state negative impact of phone use on retention of information 40% males and 43.9% females agreed that usage of mobile phone is necessary for academic success, 60.0% males and 56.10% females state that there is eyestrain by using mobile phone. 67% males and 73.5% females state that there is no anxiety by using phone. 72.2% males and 59.4% female students state headache by mobile phone usage, 53% males and 47% females’ states sleep disturbance with mobile phone use. 46% students using phone for more than 5 hours have decline in their performance. 58.10% participants have eyestrain by phone. Keywords: Impact of Mobile Phone, Mental Health, Academic Performance, Medical Students